SAT0620 Further evidences of secondary amyloidosis in alkaptonuria. (12th June 2018) - Frediani, B.; Millucci, L.; Bernardini, G.; Braconi, D.; Bardelli, M.; Marzocchi, B.; Spiga, O.; Orlandini, M.; Sestini, S.; Galeazzi, M.; Santucci, A.
Abstract : Background: Alkaptonuria (AKU) is an ultra-rare inborn error of metabolism due to a deficient activity of homogentisate 1, 2-dioxygenase. Patients suffer from a severe arthropathy. Evidence was provided on the presence of a secondary serum amyloid A (SAA)-based amyloidosis[. 1 Here a complete microscopic and ultrastructural analysis of different AKU tissues, taken from six differently aged patients, is presented. Objectives: SAA amyloidosis is a complication in AKU[, 2 making the detection of amyloid deposits at an early phase, important for treatment[. 3 We present a study of tissues from patients of different age and relevance of symptoms, providing a detailed overview of AKU amyloidosis. Methods: Different tissues were obtained from a cohort of 6 AKU patients: 4 M (63, 68, 42, 44 y) and 2 F (66, 71 y) with different severity of symptoms. Histology and amyloid were investigated. A complete microscopic and ultrastructural analysis is presented and patient features as radiological examination, mild-to-severe degenerative changes as joint space narrowing, cartilage irregularities, sub-chondral sclerosis or peripheral osteophytes and linear intervertebral disk calcifications were reported. SAAserum levels and other serological markers were measured too.Specimens were analysed by Congo Red, Immunofluorescence, Transmission Electron Microscopy. Results: The analysis of all AKU specimens confirmed the massive presence of amyloid fibrils even in young patients. Alterations in collagen composition, strictly associated to amyloid bundles deposition, were observed especially in labial salivary gland, cartilage, tendons and infrapatellar fat pad. Histological analysis showed depletion of glycosaminoglycans in young patients, whereas, at light microscopy, calcification and fibrillation were observed only in elderly patients. Immunofluorescence assessed undoubtedly the presence of SAA in amyloid deposits in AKU, and we reported for the first timethe finding of amyloid deposition in young AKU patients and in less common regions. Conclusions: We provide the first detailed overview of amyloidosis in AKU. Overall, our findings depicted a novel biological framework underlining the pathological role of amyloidosis in several AKU tissues. Furthermore, we found that degradation of extra-cellular matrixin AKU is not limited to elderly.The clinical burden of AKU may notably increase, since amyloidosis was foundeven in young AKU patients, whereas degeneration of cartilage and tendons was limited to older subjects. References: [1] Millucci L, et al. J Inherit Metab Dis2015Sep;38(5):797–805. [2] Braconi D, et al. Free RadicBiol Med2015Nov;88(Pt A):70–80. [3] Millucci L, et al. DiagnPathol. 2014Sep 26;9:185. Disclosure of Interest: None declared